Peran Orang Tua dalam Menumbuhkan Sikap Sopan Santun pada Remaja di Masyarakat Desa Tulungrejo, Kelurahan Gedog, Kecamatan Sanan Wetan, Kota Blitar - Setyowati, Raden Roro Nanik; Anggraeny, Raviva (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This research aims to describe the role of parents in cultivating courtesy attitudes among adolescents and to explain the steps taken in the process of teaching manners within the community of Tulungrejo Village, Gedog Urban Village, Sanan Wetan District, Blitar City. The background of this research stems from the phenomenon of declining courtesy attitudes among adolescents, influenced by modernization and globalization, particularly within communities that have gradually accepted changes in social values. This study employs a descriptive qualitative approach, with data collected through in-depth interviews with several parents who have adolescent children. The results of the research show that parents play an essential role in shaping courtesy attitudes among adolescents, acting as educators, role models, supervisors, counselors, and communicators. Parents also set examples by encouraging polite expressions, such as saying â€œplease,â€ â€œsorry,â€ and â€œthank you,â€ monitoring their childrenâ€™s social interactions and use of social media, and involving them in community social activities. The analysis uses Talcott Parsonsâ€™ structural functional theory, especially the four AGIL functions (Adaptation, Goal Attainment, Integration, and Latency), to explore how the family system helps maintain adolescentsâ€™ courtesy values amidst the challenges of modern times. In conclusion, the family has a significant contribution in instilling manners and courtesy, and the success of shaping adolescent character is highly determined by active parental involvement from an early age.